Corrigendum: Mapping of Urinary Schistosomiasis in Anambra State, Nigeria - Yvonne E. Ndukwe; Rose N.N. Obiezue; Ifeanyi Oscar N. Aguzie; Joy T. Anunobi; Fabian C. Okafor (Ubiquity Press, 2019)
This article details a correction to the article: Ndukwe, Y.E., Obiezue, R.N.N., Aguzie, I.O.N., Anunobi, J.T. and Okafor, F.C., 2019. Mapping of Urinary Schistosomiasis in Anambra State, Nigeria. 'Annals of Global Health', 85(1), p. 52. DOI: http://doi.org/10.5334/aogh.2393